Estudo da ocorrência de fungos e da permeabilidade em revestimentos de argamassa em habitações de interesse social estudo de caso na cidade de Pitangueiras/SP - Beato Sobrinho, Mario Marques (2008)
The construction of housing types of social concern in the city of Pitangueiras are built mostly by masonry system of self-supporting - not armed, noting that the ceramic elements mostly used are bricks (massive brick) or airbricks, and as these buildings are executed without any technical monitoring because of socioeconomic conditions that lead to this way, they eventually show all types of pathological manifestations. Relating to the pathological manifestations that come from households of social concern, the humidity rising in mortared coatings is one that most stands out mainly due to disability (or absence) of sealing in the foundations. However, some respiratory diseases are caused by fungi arising in the mould of mortared coatings. The objective of this study was to evaluate the permeability of mortared coatings in inhabitations of social concern, both in places with evidence of mould in homes and apparently sound. Also, it was tried to identify the fungi and establish relations with the occurrence of respiratory diseases in their inhabitants. The results were to assess the permeability in mortared coatings using method of testing the pipe (CSTC), classifying the homes of social interest, analyzed as "sick" or "sound". The term refers to sick with pathological manifestations and housing, the term sound healthy housing problems without pathological manifestations. It was also possible to identify the types of filamentous fungi present in the mould of coatings using the method of microbiological analysis. So it's necessary to have technical guidance in implementing the housing of social concern as regards mainly the system of sealing the foundations of painting and mortared coatings, minimizing the occurrence of diseases related respiratory to pathological manifestations found in this study.